Adjusted restricted mean survival times in observational studies - Conner, Sarah C. (Stat Med, 2019)
In observational studies with censored data, exposure-outcome associations are commonly measured with adjusted hazard ratios (HRs) from multivariable Cox proportional hazards models. The difference in restricted mean survival times (RMST) up to a pre-specified time point is an alternative measure that offers a clinically meaningful interpretation. Several regression-based methods exist to estimate an adjusted difference in RMSTs, but they digress from the model-free method of taking the area under the survival function. We derive the adjusted RMST by integrating an adjusted Kaplan-Meier estimator with inverse probability weighting (IPW). The adjusted difference in RMSTs is the area between the two IPW-adjusted survival functions. In a Monte Carlo-type simulation study, we demonstrate that the proposed estimator performs as well as two regression-based approaches: the ANCOVA-type method of Tian et al(1) and the pseudo-observation method of Andersen et al.(2–4) We illustrate the methods by re-examining the association between total cholesterol and the 10-year risk of coronary heart disease in the Framingham Heart Study.